Systems Research in Education: Designs and methods. (March 2019) - Magrath, Bronwen; Aslam, Monazza; Johnson, David
This exploratory paper seeks to shed light on the methodological challenges of education systems research. There is growing consensus that interventions to improve learning outcomes must be designed and studied as part of a broader system of education, and that learning outcomes are affected by a complex web of dynamics involving different inputs, actors, processes and socio-political contexts. How should researchers in comparative and international education respond to this call for complexity? To begin to answer this question, we draw on recent and ongoing research within the Raising Learning Outcomes in Education Systems research programme – a programme of 30 projects funded by the UK's Department for International Development (DFID) and Economic and Social Research Council (ESRC). The paper explores critical ways in which the methods used by individual research projects, and across the programme as a whole, offer opportunities and raise challenges for advancing systems thinking in education research.